2019
DOI: 10.1002/cam4.2608
|View full text |Cite
|
Sign up to set email alerts
|

CCN1 stimulated the osteoblasts via PTEN/AKT/GSK3β/cyclinD1 signal pathway in Myeloma Bone Disease

Abstract: Backgrounds: Myeloma-related bone disease (MBD) is a common complication of multiple myeloma (MM), which can both decrease life quality and influence the prognosis of the patients. We have found that CCN1 stimulated proliferation and differentiation of osteoblasts in MM in vitro and in vivo, while its mechanism still remains unknown. Method: Bone marrow mononuclear cells were collected from MM patients and differentiated into the osteoblasts. After co-culture with CCN1 in vitro, the intracellular signaling ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Glioblastoma cells also produce additional factors. For instance, the cell cycle regulator cellular communication network factor 1 (CCN1) plays an important role in cancer progression and inflammatory response in different solid cancers [56,57]. In glioblastoma, secretion of CCN1 is reported to result in macrophage infiltration in an in vivo model through the upregulation of integrins [58].…”
Section: The Influence Of Glioblastoma Cells On Tamsmentioning
confidence: 99%
“…Glioblastoma cells also produce additional factors. For instance, the cell cycle regulator cellular communication network factor 1 (CCN1) plays an important role in cancer progression and inflammatory response in different solid cancers [56,57]. In glioblastoma, secretion of CCN1 is reported to result in macrophage infiltration in an in vivo model through the upregulation of integrins [58].…”
Section: The Influence Of Glioblastoma Cells On Tamsmentioning
confidence: 99%
“…Thus, our results suggested that MondoA may promote myoblast proliferation and differentiation by activating the Akt pathway. Previous studies have shown that PTEN acts as a negative regulator of the Akt pathway and skeletal muscle fiber development [ 18 34 35 36 ]. Yue et al [ 34 35 ] demonstrated that PTEN deletion alters muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the growth-inhibiting effect was further explored by use of cyclin D1/2-specific antibodies [ 27 ]. We observed that cyclins D1/2 and Cdk4 were significantly down-regulated in IgG(NH)PAcP and wt PAcP transfected C-81 cells, approximately 70 and 30%, respectively, compared with either Prl(NH)PAcP transfected and mock transfection, despite comparable expression of the marker protein tubulin (see Figure 1 E).…”
Section: Resultsmentioning
confidence: 99%